Seawater-assisted synthesis of MnCe/zeolite-13X for removing elemental mercury from coal-fired flue gas - Zhou,Z; Liu,X; Li,C; Elvis,Cao X; Xu,M (Fuel, 2020)
To develop an efficient and low-cost sorbent for removing elemental mercury (Hg0) from chlorine-free coal-fired flue gas, the Na-13X zeolite (Z13X) was modified by the natural seawater and MnOx-CeO2. The elemental mercury removal activity over the developed sorbents was tested under a simulated coal-fired flue gas on a lab-scale fixed bed reactor. The novel sorbents were characterized by XRF, XRD, XPS, nitrogen adsorption and Hg-TPD. For the seawater-modified Z13X samples, the Cl species in the seawater were the main active species for Hg0 removal. The optimal reaction temperature was in the range of 250–350 °C. For the seawater- and MnCe oxides- comodified sorbents, the experimental results suggested that the Cl species in the seawater and the loaded metal oxides were responsible for the superior Hg0 capture activity. For the seawater modified sorbents, the best Hg0 capture activity could be achieved with loading only 1 wt% metal oxides on the Z13X. The elemental mercury removal activity tests showed that the co-modified sorbents exhibited superior and stable elemental mercury removal efficiency (>95%) for temperatures between 200 °C and 350 °C and with a flow rate-to-mass value of 2 × 105 mL/(h·g). Based on the XPS results of the surface Cl, O and metals species, the active chlorine species generated from the reactions between the adsorbed seawater chlorine and the metal oxides were responsible for enhancing the performance.